Wave Intensity Analysis Provides Novel Insights Into Pulmonary Arterial Hypertension and Chronic Thromboembolic Pulmonary Hypertension. - Su,J; Manisty,C; Parker,KH; Simonsen,U; Nielsen-Kudsk,JE; Mellemkjaer,S; Connolly,S; Lim,PB; Whinnett,ZI; Malik,IS; Watson,G; Davies,JE; et al. (Journal of the American Heart Association, 2017)
BACKGROUND: In contrast to systemic hypertension, the significance of arterial waves in pulmonary hypertension (PH) is not well understood. We hypothesized that arterial wave energy and wave reflection are augmented in PH and that wave behavior differs between patients with pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). METHODS AND RESULTS: Right heart catheterization was performed using a pressure and Doppler flow sensor-tipped catheter to obtain simultaneous pressure and flow velocity measurements in the pulmonary artery. Wave intensity analysis was subsequently applied to the acquired data. Ten control participants, 11 patients with PAH, and 10 patients with CTEPH were studied. Wave speed and wave power were significantly greater in PH patients compared with controls, indicating increased arterial stiffness and right ventricular work, respectively. The ratio of wave power to mean right ventricular power was lower in PAH patients than CTEPH patients and controls. Wave reflection index in PH patients (PAH: ≈25%; CTEPH: ≈30%) was significantly greater compared with controls (≈4%), indicating downstream vascular impedance mismatch. Although wave speed was significantly correlated to disease severity, wave reflection indexes of patients with mildly and severely elevated pulmonary pressures were similar. CONCLUSIONS: Wave reflection in the pulmonary artery increased in PH and was unrelated to severity, suggesting that vascular impedance mismatch occurs early in the development of pulmonary vascular disease. The lower wave power fraction in PAH compared with CTEPH indicates differences in the intrinsic and/or extrinsic ventricular load between the 2 diseases.